Do touch that dial: A guide to continuous response measurement in agricultural communications - Cara Lawson; Laura Fischer; Lauren LaGrande; Kelsi Opat (Journal of Applied Communications, 2020)
As the gap in agricultural experiences between farmers and consumers grow, it is important for agricultural communicators to communicate strategically with their audiences and be proactive in addressing consumers’ concerns. Communication media can present a variety of messages or pieces of information that represent multiple perspectives within one unit. The dynamic nature of communication media, such as video and audio messages, lead to the fluctuation of feelings and responses to different elements within one singular message. While agricultural communications has traditionally relied upon quantitative and qualitative survey data, there are likely gaps in complete understandings of individual perceptions in response to varying elements of the communications message. Continuous response measurement (CRM) is a method that can be used to monitor and track individual responses to media messages in real-time to reveal critical moments within a communications message. CRM holds the potential to help those in agricultural communications understand what specific elements within messages resonate most with consumers. This professional paper explores how researchers can use CRM, showcases benefits and drawbacks of CRM, and provides recommendations for contributions to agricultural communications literature.
Keywords: Continuous response measurement; sentiment analysis; message testing; methods